Chronic immune thrombocytopenia in Denmark, Sweden and Norway: The Nordic Country Patient Registry for Romiplostim. (September 2019) - Christiansen, Christian Fynbo; Bahmanyar, Shahram; Ghanima, Waleed; Risbo, Nickolaj; Ekstrand, Charlotta; Stryker, Scott; Acquavella, John; Kilpatrick, Karynsa; Frederiksen, Henrik; Nørgaard, Mette; Sørensen, Henrik Toft
Abstract: Background: Population-based cohorts of immune thrombocytopenia (ITP) are useful for understanding occurrence, clinical characteristics and long-term clinical course. This paper describes the content of the Nordic Country Patient Registry for Romiplostim (NCPRR) and provides prevalence and incidence estimates of chronic ITP (cITP). Methods: The NCPRR, a cohort study established in 2009, includes all adult (≥ 18 years) patients in Denmark, Sweden and Norway with cITP (defined as ITP lasting > 12 months and platelet count < 100 × 10 9 /L), combining data from national health registries and medical records. The NCPRR currently includes prevalent cITP patients diagnosed before 2009 and incident cITP patients diagnosed during 2009–2016. The registry obtains clinical information for cITP patients, including comorbidities, treatments, laboratory values, and complete follow-up for various outcomes. Findings: The NCPRR currently includes 3831 patients with cITP (1258 prevalent; 2573 incident). In 2009, the prevalence of registered cITP was 10 · 0/100, 000 (95%CI:9 · 1–11 · 0) adult persons in Denmark and 10 · 7/100, 000 (95% CI: 9 · 9–11 · 4) adults in Sweden. During 2009–2016, the incidence rates of cITP per 100, 000 person-years were 2 · 8 (95%CI: 2 · 6–3 · 0), 1 · 8 (95%CI: 1 · 7–1 · 9) and 2 · 1 (95%CI: 1 · 9–2 · 2) in Denmark, Sweden and Norway, respectively. Fifty-eight percent of cITP patients were women. At NCPRR inclusion, 30.2% were aged ≥ 70 years, 23% had a platelet count < 50 × 10 9 /L, 17.4% were splenectomized, 41% had prior ITP therapy, and 8.6% had severe comorbidity. Interpretation: The NCPRR provides population-based data on the epidemiology and characteristics of almost 4000 cITP patients and is a valuable resource for research. Funding: This study was partly funded by a research grant from Amgen to Aarhus University.